THE REFLECTION OF PROCEDURAL GUILT IN THE CRIMINAL PROCEDURE PROVISIONS. LIABILITY FOR UNJUST CONDEMNATION OR FOR TAKING PREVENTIVE MEASURES UNLAWFULLY - ELIZA EMANUELA OPREA (Challenges of the Knowledge Society)
In the criminal proceedings of some law states the wrongful sentencing of individuals is very rare, having a comprehensive system of procedural safeguards which prevent such a situation. The purpose of the criminal proceedings is to punish only the culprits, the Criminal Procedure code frontispiece being stated the idea that no innocent person should be held criminally liable. By achieving this aspect of purpose is ensured observance of legality and the rule of law. All the basic rules and the whole organization of the criminal trial are polarized around this major goal of justice. Also the professional qualification level of those summoned to administer criminal justice in the modern state to minimizes the risk of judiciar miscarriages. The deep humanism of our law requires though the regulation of those procedural arrangements, through which in the event of an act of injustice, the wrongly convicted is able to obtain prompt repairs that society owes them. A very important aspect related to the evolution over time of the regulation of this institution, is that in its doctrine of integration in the European Union, Romania has adopted a series of laws and regulations designed to ensure our legislation’s alignment with the relevant legislation of the countries from the European community and to ensure the compliance with the European Convention on Human Rights. This process is still ongoing, therefore the establishment and the subsequent modification of the special procedure concerning the remedies for the material or moral damage in the event of unjust sentence or unlawful deprivation of liberty was based on the desire to avoid the conviction situation of the Romanian state by the international courts for failure to comply with the Art. 5 paragraph 5 of the Convention for the Protection of Human Rights and Fundamental Freedoms that 'any individual who is the victim of arrest or detention in conditions contrary to the provisions of this article shall have the right for remedy".